THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND MENTAL HEALTH WITH ANXIETY LEVELS IN FACING THE DELIVERY PROCESS INPREGNANT WOMEN IN THE THIRD TRIMESTER AT THETEKUNG COMMUNITY HEALTH CENTER,LUMAJANG REGENCY IN 2025 - Cifki Widyawati Cipta Devi; Wahida Yuliana; Farianingsih (Lppm Unan, 2026)
Background; Anxiety in pregnant women during labor is a common psychological condition caused by fear of pain, medical complications, and uncertainty about the outcome of labor. Factors such as previous experience, support from family and medical personnel, and information about childbirth can influence anxiety levels. With this background, the researcher aimed to explore the relationship between family support and mental health and anxiety levels during labor among pregnant women in their third trimester at the Tekung Community Health Center, Lumajang Regency, in 2025. Methods: The research design is a plan or plan created by the researcher as a framework for the activities to be implemented. This analytical survey used a cross-sectional approach. Results: The results of the rho test indicated a p-value of 0.00 with a significance level (α) <0.05. Because the p-value is less than α, H₀ is rejected and H₁ is accepted. This indicates that there is a relationship between family support and the level of anxiety in facing the delivery process in pregnant women in the third trimester at the Tekung Health Center, Lumajang Regency in 2025, and there is a relationship between mental health and the level of anxiety in facing the delivery process in pregnant women in the third trimester at the Tekung Health Center, Lumajang Regency in 2025. Conclusion; The results of the study showed that there was a relationship between family support and the level of anxiety in facing the delivery process in pregnant women in the third trimester at the Tekung Health Center, Lumajang Regency in 2025 and there was a relationship between mental health and the level of anxiety in facing the delivery process in pregnant women in the third trimester at the Tekung Health Center, Lumajang Regency in 2025.